First identification of Krüppel-like factor 2 mutation in heritable pulmonary arterial hypertension - Eichstaedt, Christina; Song, Jie; Rodríguez Viales, Rebecca; Pan, Zixuan; Benjamin, Nicola; Fischer, Christine; Hinderhofer, Katrin; Grünig, Ekkehard (Clinical science, 2017)
Heritable pulmonary arterial hypertension (HPAH) is an autosomal dominantly inherited disease caused by mutations in the bone morphogenic protein receptor 2 (BMPR2) gene and/or genes of its signalling pathway in approximately 85% of patients. We clinically and genetically analysed an HPAH family without mutations in previously described pulmonary arterial hypertension (PAH) genes. Clinical assessment included electrocardiogram, lung function, blood gas analysis, chest X-ray, laboratory testing, echocardiography and right heart catheterization in case of suspected disease. Genetic diagnostics were performed using a PAH-specific gene panel including all known 12 PAH genes and 20 further candidate genes by next-generation sequencing (NGS). HPAH was invasively confirmed in two sisters and their father who died aged 32 years. No signs of HPAH were detected in five first-degree family members. Both sisters were lung transplanted and remained stable during a follow-up of >20 years. We detected a novel missense mutation in the Krüppel-like factor 2 (KLF2) likely leading to a disruption of gene function. The same KLF2 mutation has been described as a recurrent somatic mutation in B-cell lymphoma. Neither the healthy family members carried the mutation nor >120000 controls. These findings point to KLF2 as a new PAH gene. Further studies are needed to assess frequency and implication of KLF2 mutations in PAH patients.
Gesehen am 28.11.2018